1995
DOI: 10.1152/jappl.1995.78.6.2228
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen effect on O2 deficit and VO2 kinetics during exercise in obstructive pulmonary disease

Abstract: We evaluated the effect of supplemental O2 on energy metabolism of hypoxemic humans by measuring O2 uptake (VO2) kinetics and other cardiorespiratory parameters in nine male chronic obstructive pulmonary disease (COPD) patients and seven age-matched control subjects (on air and on 30% O2) at rest and during moderate cycle ergometer exercise. Heart rate, ventilation, VO2, CO2 output, respiratory exchange ratio, O2 cost of work, and work efficiency were measured with a computerized metabolic cart; O2 deficit and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 0 publications
4
50
1
Order By: Relevance
“…4 ("no delay in O 2 delivery") represents the expected response of speeding O 2 delivery, as was shown in this model in the past (15). These results may have applications to those disease states in which the V O 2 on-kinetics response is slowed (3,6,7,9,14,19,44,51,52,55) and/or the rate of convective O 2 delivery at the onset of contractions is impaired (3,6,7,44,46,52). Specifically, we have shown that this isolated muscle operates precariously close to a tipping point whereby any slowing of O 2 delivery slows the V O 2 on-kinetics during the transition to a submaximal metabolic rate (Ϸ50 -70% V O 2peak ).…”
Section: Discussionsupporting
confidence: 55%
“…4 ("no delay in O 2 delivery") represents the expected response of speeding O 2 delivery, as was shown in this model in the past (15). These results may have applications to those disease states in which the V O 2 on-kinetics response is slowed (3,6,7,9,14,19,44,51,52,55) and/or the rate of convective O 2 delivery at the onset of contractions is impaired (3,6,7,44,46,52). Specifically, we have shown that this isolated muscle operates precariously close to a tipping point whereby any slowing of O 2 delivery slows the V O 2 on-kinetics during the transition to a submaximal metabolic rate (Ϸ50 -70% V O 2peak ).…”
Section: Discussionsupporting
confidence: 55%
“…7) has also been used to detect improvements in oxygen transport and/or skeletal muscle metabolism after a specific intervention [255,271,272]. The V9O 2 kinetics reflect the overall efficiency of the oxygen transport system including muscle oxidative capacity and, in COPD, seem to be influenced by the oxygen delivery to the working muscles [273].…”
Section: Symptom-limited Incremental Testmentioning
confidence: 99%
“…Enhancing oxygen delivery through hyperoxia has been demonstrated to enhance performance during maximal incremental exercise in healthy subjects (Prieur et al, 2002), and during high intensity constant load exercise in both healthy subjects and COPD (Siqueira et al, 2010;Wilkerson et al, 2006). Whilst such interventions have no effect on the fundamental phase of pulmonary oxygen uptake kinetics in healthy subjects, (Hughson and Kowalchuk, 1995;Wilkerson et al, 2006), this has been shown to be speeded by hyperoxia and heliox in COPD (Chiappa et al, 2009;Palange et al, 1995). Infusion of L-NAME speeded pulmonary oxygen uptake kinetics at the onset of moderate and heavy exercise in healthy subjects, possibly by relieving inhibition of enzymes in the electron transport chain (Jones et al, 2003;Jones et al, 2004a); such studies have not however been replicated in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In COPD, a lag in the activation of the PDC (Calvert et al, 2008) and delivery of oxygen (Chiappa et al, 2008;Chiappa et al, 2009;Laveneziana et al, 2009;Palange et al, 1995) have both been shown to be limiting to oxidative metabolism during the transition from rest to exercise. The tricarboxylic (TCA) cycle and its intermediates (TCAi) do not seem to limit oxidative metabolism during the transition from rest to exercise in healthy populations, (Bruce et al, 2001), however there is evidence that the TCAi may be a limiting factor for oxidative metabolism in COPD.…”
Section: Introductionmentioning
confidence: 99%